Pemasaran Produk Berbasis Online Bagi Pengusaha Ritel Mandiri di Desa Pancasari, Buleleng - I Made Astu Mahayana; I Gusti Ayu Agung Dian Susanthi; Ni Kd Sioaji Yamawati; I Wayan Budiarta; I Nyoman Mardika (Linguistic Community Services Journal, 2021)
New Normal life has again given hope to traders in Pancasari Village, Sukasada, Buleleng, Bali. The wheels of the economy are turning again, of course, by implementing health protocols, traders are allowed to reopen their businesses. This is a new challenge for retail owners; they had to think of various ways to restart a business that had been out of operation for several months. Online business is the latest solution in this era of society 5.0. Products or services advertised (marketed) online, of course, must be attractive so that they can be of interest to buyers. These products can be offered online through social media. This is a new experience for retail owners, especially in the village of Pancasari, Sukasada District, Buleleng which usually offers its merchandise conventionally. This PKM is carried out with the aim of helping independent retail entrepreneurs in Pancasari Village, Sukasada District, Buleleng Regency, who have never been familiar with online marketing. This PKM is carried out by recording partner knowledge, disseminating information to partners, providing training to partners, and monitoring partner business developments. Based on the results of the discussion above, two products, namely coffee drinks and food seasonings, have distinctive features in the choice of words used. In coffee drink products, the verbs chosen are enjoy, taste, and feel. While the selected adjectives are delicious, delicious, distinctive, and perfect. In seasoning/food products, the verbs chosen are try, taste, and taste. While the selected adjectives are delicious, delicious, distinctive, and best.